2004
DOI: 10.1016/j.eurpsy.2003.06.009
|View full text |Cite
|
Sign up to set email alerts
|

DSM-IV mental disorders and neurological complications in children and adolescents with human immunodeficiency virus type 1 infection (HIV-1)

Abstract: - The very low % of CD4 lymphocytes of these children suggest that the appearance of a psychiatric complication should be regarded as a factor indicating severe HIV infection. Depressive disorders may be a clinical form of encephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 6 publications
3
21
0
Order By: Relevance
“…Attention-deficit/hyperactivity disorder (ADHD) has been reported to be the most common psychiatric diagnosis among perinatally infected youths, ages 5-12 (Havens et al 1994), a finding later confirmed in a study conducted by the Women and Infant Transmission Study Group (Mellins et al 2003). More recently, depression and attentional disorders have been reported to be a common psychiatric manifestation in HIV-infected youth ages 6-15 with a possible association between depression and the presence of HIV encephalopathy (Misdrahi et al 2004).…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Attention-deficit/hyperactivity disorder (ADHD) has been reported to be the most common psychiatric diagnosis among perinatally infected youths, ages 5-12 (Havens et al 1994), a finding later confirmed in a study conducted by the Women and Infant Transmission Study Group (Mellins et al 2003). More recently, depression and attentional disorders have been reported to be a common psychiatric manifestation in HIV-infected youth ages 6-15 with a possible association between depression and the presence of HIV encephalopathy (Misdrahi et al 2004).…”
Section: Introductionsupporting
confidence: 54%
“…Consequently, most perinatally HIV-infected children are surviving into their adolescent and young adult years (Gortmaker et al 2001). Unfortunately, data suggest that in this population of survivors there is a high rate of psychiatric symptoms (Havens et al 1994;Battles and Wiener 2002;New et al 2003;Mellins et al 2003;Misdrahi et al 2004;Wiener and Battles, in press) and psychiatric hospitalizations (Gaughan et al 2004) compared with the general pediatric population (Lewinsohn et al 1993;Reinherz et al 1993;Shaffer et al 1996;Olfson et al 2005). Little is known about psychotropic medication use among a cohort of adolescent survivors receiving long-term HIV treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was limited by small sample sizes and few controlled studies. Others suggest that depression and attentional problems are common psychiatric manifestations in HIV-infected youths 6 to 15 years old [20]. One study described higher rates of psychiatric hospitalization among perinatally infected children and adolescents compared with their non-HIVinfected peers and noted that the primary reasons for admission include depression and behavioral problems (eg, ADHD and oppositional defiant disorder) [21].…”
Section: Psychopathology and Hiv Diseasementioning
confidence: 98%
“…[1][2][3] Although there are a number of studies that document the prevalence of psychological symptoms among children living with HIV, [4][5][6][7] there are fewer that address this issue among adolescents, and none with a large cohort of behaviorally infected youth in this era of simplified treatment regimens. Examination of psychological symptoms and emotional distress among adolescents living with HIV is critical because they are associated with worse quality of life, 8,9 poorer health, 8,10 less adherence to antiretroviral medication (increasing the likelihood for secondary transmission of HIV), [11][12][13][14] greater substance use, 6,[15][16][17] and more sexual risk behavior.…”
mentioning
confidence: 99%